The role of YouTube platform as a learning resource in online learning effectiveness - Diva Fikri Harry Adnan; Norma Istiqomah (Curricula: Journal of Curriculum Development, 2022)
The COVID-19 pandemic has resulted in teachers using media more creatively in the learning process, one of which is using video-based media via YouTube. This study aims to find out the role and implementation as well as the obstacles that arise in using YouTube as a learning resource in supporting the effectiveness of online learning based on the perceptions or views of students. The research uses quantitative methods with primary data sources and data collection using surveys or questionnaires involving active students as respondents. The study results show that most respondents agree that using YouTube is a practical learning resource or online learning media. However, there are still some obstacles encountered in practice. So, the YouTube platform had a good impact on the effectiveness of online learning during the COVID-19 pandemic and increased opportunities for using YouTube as a learning media.